A Novel Method for Preparation of Carrageenan/Fish Scale Collagen/Allopurinol Biocomposite Film - Quoc Manh Vu; Thuy Chinh Nguyen; Duong My Ngoc Dam; Quoc Trung Vu; Trong Lu Le; Tran Dung Hoang; Thi Kim Ngan Tran; Tuan Anh Nguyen; Phi Hung Nguyen; Hoang Thai (International Journal of Polymer Science)
Biopolymers such as carrageenan or collagen can be used as carriers for loading a drug to enhance a drug’s bioavailability. In this work, allopurinol was loaded on a carrageenan/collagen blend and the carrageenan/collagen/allopurinol (CCA) biocomposite films were prepared using the ionic gelation method combined with the 3D printing method using carrageenan/collagen/allopurinol gel as a 3D printing ink material. The advantages of the 3D printing method are the ease in shaping the design of films and the ease in controlling the thickness of films. The results of infrared (IR) spectroscopy and field emission scanning electron microscopy (FESEM) analyses showed that the CCA biocomposite films have a regular structure, and the functional groups of components in the biocomposites can interact with each other. After 30 minutes of immersion in distilled water and pH buffer solution, the biocomposite films swelled and disintegrated. The carrageenan/collagen blend can control the release of allopurinol in simulated body fluids. In addition, the drug release kinetic models reflecting the release process of allopurinol from CCA biocomposite films in simulated body fluids have also been calculated.